Emergency contraception: knowledge, attitude and practices among recently married females in a rural area of North India - Gupta, Rajiv Kumar; Singh, Parveen; Gupta, Chandini; Kumari, Rashmi; Langer, Bhavna; Gupta, Riya (International Journal of Research in Medical Sciences, 2017)
Background: Emergency contraception (EC) is indicated after unprotected sexual intercourse to prevent unintended pregnancy and its harmful consequences. Its optimum use can avoid unintended child birth or unsafe abortion which can in turn lower maternal mortality. So, the present study aimed to study the knowledge, attitude and practices of recently married females towards EC in a rural area of Jammu. Methods: The present cross-sectional study was conducted among recently married females visiting the OPD in CHC RS Pura during the course of the three months and were willing to participate. Information was obtained using a questionnaire and results were presented as proportions. Results: 90% respondents had ever heard of EC with media being the main source of information. 91% knew oral pills being used as EC and 81% had correct knowledge of time regarding its usage. 85% would recommend it to friend/relative if required and 73% were willing to use EC themselves in case of unprotected sex. 70% of the respondents had ever used EC. Conclusions: High awareness, positive attitude and adequate usage of EC among currently married females is a good sign which is probably due to high literacy among them. But it should not make the authorities complacent, rather interventions intended to combat maternal mortality through use of regular contraceptives besides EC need to be promoted among the target groups.